Implications of alpha-decay for long term storage of advanced heavy water reactor fuels. (December 2017) - Pencer, J.; McDonald, M.H.; Roubtsov, D.; Edwards, G.W.R.
Highlights: Alpha decays versus storage time are calculated for examples of advanced heavy water reactor fuels. Estimates are made for fuel swelling and helium bubble formation as a function of time. These predictions are compared to predictions for natural uranium fuel. Higher rates of damage are predicted for advanced heavy water reactor fuels than natural uranium. Abstract: The decay of actinides such as 238 Pu, results in recoil damage and helium production in spent nuclear fuels. The extent of the damage depends on storage time and spent fuel composition and has implications for the integrity of the fuels. Some advanced nuclear fuels intended for use in pressurized heavy water pressure tube reactors have high initial plutonium content and are anticipated to exhibit swelling and embrittlement, and to accumulate helium bubbles over storage times as short as hundreds of years. Calculations are performed to provide estimates of helium production and fuel swelling associated with alpha decay as a function of storage time. Significant differences are observed between predicted aging characteristics of natural uranium and the advanced fuels, including increased helium concentrations and accelerated fuel swelling in the latter. Implications of these observations for long term storage of advanced fuels are discussed.